(untitled) (Bangladesh Journal of Microbiology, 2010)
Six isolates of Rhizobium were isolated from pea (Pisum sativum) to characterize their cultural properties and observe their effectiveness on host legume. In a laboratory study Rhizobium isolates showed characteristic pattern of reactions in respect of growth rate, colony characteristics and acid/alkali production on different growth media. The effect of inoculations of Rhizobium isolates on nodulation, growth and nitrogen fixation of pea were assessed by a pot experiment on a clay loam soil of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur. Inoculation treatments comprised of Rhizobium isolates R1, R2, R3, R4, R5 and R6. Among the Rhizobium isolates R3 and R5 of pea at 50% flowering stage had significant positive effective on nodulation, growth and nitrogen fixation of pea. There were high positive correlations among the number and dry weight of nodules, N content and uptake by shoot of pea. Keywords: Rhizobium; Pea; Nodulation; Growth; Nitrogen fixation DOI: http://dx.doi.org/10.3329/bjm.v25i1.4855 Bangladesh J Microbiol, Volume 25, Number 1, June 2008, pp 45-48